Improving voltage unbalance of low-voltage distribution networks using plug-in electric vehicles. (1st April 2017) - Farahani, Hassan Feshki
Abstract: Plug-in electric vehicles are one of the clean technologies that have many advantages to overcome the problems of power systems for instance voltage unbalance in distribution networks. Considering coordinated or uncoordinated charging method, voltage unbalance factor can be improved or worsened. In real applications, most PEVs are connected to residential or commercial networks in the form of single-phase and they can be charged or discharged that leads to voltage unbalance. In this paper, the effect of PEVs on network voltage unbalance is investigated in the form of optimization problem. VUF is minimized as an objective function in different conditions, subject to network security and PEVs constraints, using PSO algorithm. VUF is minimized by optimally selecting the state of PEVs (charging or discharging), PEV point of connection (phase a, b or c ) and charging/discharging rating power. Also, the impact of uncoordinated and coordinated charging of PEVs on VUF is evaluated. Besides, the effectiveness of the proposed framework is studied based on an unbalanced three-phase distribution network. Finally, the obtained results show that coordinated charging/discharging of PEVs can significantly improve VUF value.